Faktor-Faktor yang Menentukan Keterlibatan Pemuda Pedesaan pada Kegiatan Pertanian Berkelanjutan - Fitri Ningsih; Sofyan Syaf (Jurnal Penyuluhan, 2015)
Sustainable agriculture is one of national goal development in the realization of food self-suffiency in Indonesia. Sustainable agriculture will not be realized without the involvement of youth in agricultural activities, which include the activities of land and seed preparation, maintenance, and harvesting. Agricultural activities must be able to meet the economic needs, maintaining land fertility, and recognized by society as decent job. The purpose of this research was to analyze the factors that determine the involvement of rural youth in sustainable agricultural activities. In order to achieve that, the research methodology used qualitative and quantitative methods. Methodology used for quantitative is survey approach. Quantitative data were processed using regression test, rank Spearman test, and cross tabulation. Meanwhile, methodology that used for qualitative is in-depth interview approach. Data obtained from this method were reduced, presented, and drawn for conclusion. Result of the research showed the involvement of youth in agricultural activities had became decreased due to parental socialization and low cohesiveness peers. Agricultures was considered as a job that is not economically viable. Therefore, it needs attention of various sides to improve the socialization of agriculture, and coordinate the institution to facilitate youth sharing information about agriculture.Keywords: rural youth, agricultural activities, sustainable agriculture, development